Costs and resource use following defunctioning stoma in low anterior resection for cancer – A long-term analysis of a randomized multicenter trial. Issue 2 (February 2017) - Floodeen, H.; Hallböök, O.; Hagberg, L.A.; Matthiessen, P.
Abstract: Background: Defunctioning stoma in low anterior resection (LAR) for rectal cancer can prevent major complications, but overall cost-effectiveness for the healthcare provider is unknown. This study compared inpatient healthcare resources and costs within 5 years of LAR between two randomized groups of patients undergoing LAR with and without defunctioning stoma. Method: Five-year follow-up of a randomized, multicenter trial on LAR (NCT 00636948) with (stoma; n = 116) or without (no stoma; n = 118) defunctioning stoma comparing inpatient healthcare resources and costs. Unplanned stoma formation, days with stoma, length of hospital stay, reoperations, and total associated inpatient costs were analyzed. Results: Average costs were € 21.663 per patient with defunctioning stoma and € 15.922 per patient without defunctioning stoma within 5 years of LAR, resulting in an average cost-saving of € 5.741. There was no difference between groups regarding the total number of days with any stoma (stoma = 33 398 vs. no stoma = 34 068). The total number of unplanned reoperations were 70 (no stoma) and 32 (stoma); p < 0.001. In the group randomized to no stoma at LAR, 30.5% (36/118) required an unplanned stoma later. Conclusion: Randomization to defunctioning stoma in LAR was more expensive than no stoma, despite the cost-savings associated with a reduced frequency of anastomotic leakage. Both groups required the same total number of days with a stoma within five years of LAR.